2015
DOI: 10.1002/lary.25695
|View full text |Cite
|
Sign up to set email alerts
|

Nonmotor disabilities in patients with facial palsy measured by patient-reported outcome measures

Abstract: 4. Laryngoscope, 126:1516-1523, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 30 publications
4
23
0
1
Order By: Relevance
“…It is well documented that general questionnaires such as those on the SF-36 have low sensitivity to facial palsy. 44,51 We believe that we have replicated such findings through our use of the FDI; facial nerve function does not seem to impact general questions on QOL assessments. Interestingly, however, the social/well-being evaluation of the symptom-specific FDI questionnaire demonstrated that the MS cohort had results similar to those of the healthy controls despite the reduced HB grade of the former group.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…It is well documented that general questionnaires such as those on the SF-36 have low sensitivity to facial palsy. 44,51 We believe that we have replicated such findings through our use of the FDI; facial nerve function does not seem to impact general questions on QOL assessments. Interestingly, however, the social/well-being evaluation of the symptom-specific FDI questionnaire demonstrated that the MS cohort had results similar to those of the healthy controls despite the reduced HB grade of the former group.…”
Section: Discussionsupporting
confidence: 53%
“…2,26,49 Some of these studies have compared general quality of life (QOL) following treatment-but it is well known that general QOL inventories such as the 36-Item Short Form Health Survey (SF-36) are less sensitive to facial nerve weakness. 44,51 Microsurgery (MS) provides a high cure rate when a tumor is completely removed and remains, according to some authors, the preferred treatment modality for small-and medium-sized VSs, especially in younger patients. 25,29,53,56 Given improvements in microsurgical techniques over the past several decades and the introduction of intraoperative electrophysiological monitoring of the facial nerve, the incidence of facial nerve injury associated with VS microsurgery has declined significantly.…”
mentioning
confidence: 99%
“…It can be a devastating and disfiguring condition, leading to psychological difficulties and restrictions of facial expressions, and may have a dramatic impact on interpersonal relationships. 1 The impact of FP on quality of life (QoL) is well known, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] although sometimes no correlation has been found between severity of FP and QoL. [3][4][5][6]8,20 When it has been found, the correlation ranges from 0.13 to 0.66, 2,10,12,14,15,17,21,22 meaning that other factors may be important contributors to QoL in patients with FP.…”
Section: Introductionmentioning
confidence: 99%
“…The clinician's overall impression of the patient is taken as standard and is assumed to represent the degree of abnormality of facial function [1, 2, 4-6, 8, 26-36]. This enables clinicians to keep track of patients' recovery and evaluate the efficacy of treatment [4,28,31,37]. FNP is assessed using grading scales that typically measure patients' facial function, grade symmetry of the face at rest, and measure displacement of facial features during voluntary movement, as well as the presence of synkinesis.…”
Section: Introductionmentioning
confidence: 99%